2019
DOI: 10.1093/jn/nxz157
|View full text |Cite
|
Sign up to set email alerts
|

Height Trajectory During Early Childhood Is Inversely Associated with Fat Mass in Later Childhood in Mexican Boys

Abstract: Background Childhood obesity continues to be a global health problem. Previous research suggests that linear growth retardation or stunting during early childhood increases the risk of obesity, but others have reported that rapid linear growth poses a greater concern than early nutritional status. Objective The objective of this study was to determine if growth trajectories are associated with body composition at age 8–10 y. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In the context of the double burden of malnutrition, dietary advice must consider malnutrition in all its forms (Zarate-Ortiz et al 2019). Gain in height among boys, but not in girls, in early childhood, was associated with lower adiposity in late childhood compared with children with a slower rate of growth (Barrios et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the double burden of malnutrition, dietary advice must consider malnutrition in all its forms (Zarate-Ortiz et al 2019). Gain in height among boys, but not in girls, in early childhood, was associated with lower adiposity in late childhood compared with children with a slower rate of growth (Barrios et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have explained the presence of excessive weight in people with food insecurity through physical and mental mechanisms. For instance, growth failure in fetal life and infancy, which is especially associated with food insecurity in low-income communities (Borders et al, 2007;Chowdhury et al, 2018), has been correlated with higher visceral fat in adult life (Barrios et al, 2019;Corvalan et al, 2007;Law et al, 1992;Schroeder et al, 1999). According to Martins et al (2004) this association can be explained since chronic undernutrition in infancy is correlated to metabolic adaptations that further lead to higher fat mass accumulation.…”
Section: Food Security and Obesity Pathwaysmentioning
confidence: 99%
“…Cross-sectional studies in Brazil found that stunted school-aged children were more obese and had greater abdominal circumferences than non-stunted children [ 7 ]. Stunted boys in Brazil and in Mexico with slower height gain had greater FM and lower FFM compared to non-stunted boys or boys with greater height gain [ 23 , 24 ]. No significant differences were found between stunted and non-stunted girls or among girls with different growth trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a categorical variable for the SES measure was created with missing values categorized as zero, values below the median of summed processions classified as one, and values greater than the median classified as two. Models were adjusted for weight to distinguish body composition compartments as children with greater height had a higher body weight compared with children with the low-growth classes [ 24 ]. All statistical tests were performed using SPSS ® 26 (IBM Corporation; Armonk, NY, USA) with statistical significance defined as p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation